Role of Competence Perception in Predicting Emotional Self-Awareness and Bullying and Victim Behavior in Elementary Students. - Reyhane Rakhshani nejad; Zahra Nikmanesh (مطالعات روانشناسی تربیتی)
The purpose of this study is the investigation of the role of competence perception in predicting emotional self-awareness and bullying and victim behavior in elementary students. The research method was descriptive-correlational. The statistical population was were 1200 Zahedan elementary school students in the year 1398. The 268 numbern of the students (138 girls, 130 boys) were selected by random multi-stage cluster sampling. The variables were measured using the Harter competency perception questionnaire (1982), Tanjani et al. (1990) emotional self-awareness questionnaire, and Rigby and Esley bullying-victim (1993). Data were analyzed using Pearson correlation and regression methods. The results showed that emotional self-awareness was positively and positively correlated with competency perception (r = 0.675, P <0.001) and has negatively correlated with bullying with competency perception (r = -0.547, P <0.001). Inaddition, with a one score of change in competency perception, emotional self-awareness and bullying-victim behavior change 0.67 and -0.54, respectively. According to the results, it is concluded that by increasing students' perception-competence, they can increase their emotional self-awareness and reduce bullying behavior.